A randomized controlled trial of mobile intervention using health support bubbles to prevent social frailty - Chisato Hayashi; Nanae Tanemura; Maki Taniguchi; Tadashi Okano; Hiromitsu Toyoda; Sonoe Mashino; Soshiro Ogata (npj Digital Medicine)
Abstract Mobile health (mHealth) is gaining interest worldwide. This randomized trial aimed to test the effects of family companionship on the prevention of social frailty among Japanese individuals aged ≥40 years using a mHealth application. We used a participant-coaching system, which included a mobile nutrition management software application and a web portal. We assessed social frailty using Bunt’s framework. We enrolled 101 participants who used the application either alone (control group) or with family members (intervention group). The intervention arm showed greater improvement in social behavior and leisure activities (p = 0.004) and the total frailty score (p = 0.037). However, the social isolation did not improve with intervention. Our results suggest that mHealth can influence behavior change, but it does not resolve social isolation. While it provides convenience and enhanced access to healthcare, there is a need to balance digital efficiency with human interaction, ensuring that mHealth solutions complement, rather than replace, personal connections.